2009
DOI: 10.1152/ajprenal.90548.2008
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise attenuates caspase-3 activity, oxidative stress, and inhibits progression of diabetic renal disease indb/dbmice

Abstract: Diabetic nephropathy, the leading cause of end-stage renal disease, is characterized by a proapoptotic and prooxidative environment. The mechanisms by which lifestyle interventions, such as exercise, benefit diabetic nephropathy are unknown. We hypothesized that exercise inhibits early diabetic nephropathy via attenuation of the mitochondrial apoptotic pathway and oxidative damage. Type 2 diabetic db/db and normoglycemic wild-type mice were exercised for an hour everyday at a moderate intensity for 7 wk, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 48 publications
7
88
2
2
Order By: Relevance
“…For example, low-intensity exercise was shown to attenuate the progression of diabetic nephropathy in KK-A (Y) mice 30 and db/db mice. 31 Swimming exercise reduced the progression of renal disease in 5/6 nephrectomized rats. 32 Previous exercise training also protects against the progression of diabetic nephropathy produced by streptozotocin-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 98%
“…For example, low-intensity exercise was shown to attenuate the progression of diabetic nephropathy in KK-A (Y) mice 30 and db/db mice. 31 Swimming exercise reduced the progression of renal disease in 5/6 nephrectomized rats. 32 Previous exercise training also protects against the progression of diabetic nephropathy produced by streptozotocin-induced diabetes in rats.…”
Section: Discussionmentioning
confidence: 98%
“…Oxidative stress induced by superoxide anion excess is considered a major cause of DN [26][27][28][29]. We have recently reported that renal oxidative stress is highly produced in the incipient DN stage, but not the normoalbuminuric stage, and that the incipient DN stage is more suitable than other stages for antioxidative intervention [30].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced lipid peroxidation was estimated by direct quantification of lipid hydroperoxides in heart tissue using a commercial kit (Cayman Chemicals) as described previously (23). Plasma triglycerides were quantified by a commercial colorimetric kit (Wako Diagnostics).…”
Section: Methodsmentioning
confidence: 99%